Exploring the Depth and Breadth of The Digital Divide in Developing Countries: The Case of Pakistan - Zaidi, Mosharraf (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
One of the primary tasks confronting governments, civil society and international agencies in developing countries continues to be a reduction in the level and incidence of poverty, as well as the gap between the affluent and the poor. This income and wealth "divide" is reflected in a spectrum of such additional indicator of the human condition as education, healthcare, and gender empowerment.